Comparative advantage and skill-specific unemployment - Mario Larch; Wolfgang Lechthaler (Kiel Institute for the World Economy (IfW), 2009)
We introduce unemployment and endogenous selection of workers into different skill-classes in a trade model with two sectors and heterogeneous firms. This allows us to study the distributional consequences and the skill-specific unemployment effects of trade liberalization. We show that the gains from trade will be distributed very unequally. While unskilled workers loose in terms of real wages and employment levels in the skilled labor intensive sector, skilled workers loose in terms of real wages and unemployment levels in the unskilled labor intensive sector. However, the inequality of workers between sectors is much larger for skilled labor than for unskilled labor. On average, unemployment among unskilled workers increases when a skill-abundant country opens up to trade.
Keywords: F11; F12; F16; J64; L11; 330; Comparative advantage; heterogeneous firms; labor market frictions; unemployment; trade liberalization; Außenhandelsliberalisierung; Komparativer Kostenvorteil; Qualifikation; Arbeitslosigkeit; Ungelernte Arbeitskräfte; Lohnstruktur; Theorie